Development of the Mystery Box Learning Media in Pancasila Education for 5th Grade Students at SDN 08 Tiumang - Nanda, Dodi Widia; Karmila, Desi; Fitriana, Nora (The Future of Education Journal, 2025)
This research is motivated by the low learning interest, lack of critical thinking skills, and the quick boredom students experience while participating in Pancasila education lessons. The use of learning media such as textbooks and educational videos still cannot address these issues because of their monotonous presentation and lack of interactivity. Therefore, there is a need for innovative learning media that can capture students' attention and make them more active and engaged in the learning process. The method used in this study is R&D (Research and Development), a research method used to develop or validate products used in investigation and learning. The R&D approach provides systematic steps, starting from problem identification, product design, trials, to revisions and product refinement. This study aims to develop a learning media in the form of a mystery box, a 3-dimensional visual media designed to effectively deliver the material on the history of Pancasila formulation. The specific goal of this research is to produce a valid, practical, and effective mystery box media for implementation in Pancasila education for 5th grade students at SDN 08 Tiumang. Based on the research results, the effectiveness of the mystery box learning media can be seen from the learning outcomes of the 5th-grade students at SDN 08 Tiumang, with a total of 9 students. The study aimed to determine whether students' scores could meet the determined KKTP (Minimum Completion Standard). According to the conducted research, the effectiveness percentage based on student learning outcomes was 81%, with 9 students completing the KKTP and 1 student not completing it. This suggests that the mystery box learning media is effective.